The sociologies of the individual revisited. Explorations between social supports, reflexivities and decenterings of modernity - Aliano, Nicolás (2019)
The article aims to present a map of contemporary debates around the study of social processes of individuation. Firstly, we analize the developments of contemporary french sociology around the “social supports” of the person, and the developments of brazilian social sciences about dimensions of the constitution of empirical forms of social agent. Then, we seeks to identify the main analytical matrices that have guided the study of processes of individuation in contemporary Argentina, with special emphasis on the analysis of these processes in the popular world. The inquiry is completed with the presentation of a balance of contributions of these explorations, and the challenges in this field of studies.